Integrated Approach for Liming and Fertilizer Application on Yield of Cabbage and Cauliflower in Acidic Soil of Sylhet - Nazrul, MI; Shaheb, MR (Bangladesh Agronomy Journal, 2016)
An experiment was conducted at farming system research and development (FSRD) site, Jalalpur and multi location testing (MLT) sites, Moulvibazar and Zokigonj during 2013-2015 to study the effect of liming and fertilizers levels on the yield of cabbage and cauliflower in acidic soil of Sylhet. Trials were laid out in a factorial randomized block design with six dispersed replications. The treatments of fertilizer managements were M1: soil test based (STB) recommended fertilizer and M2: fertilizer dose practiced by the farmers (FP) and the level of limes were L1:0 t ha-1; L2: 1 t ha-1 and L3: 2 t ha-1. Results revealed that yields of cabbage and cauliflower responded significantly to fertilizer doses, levels of lime, and their combinations in all the locations. Soil test based fertilizer rate (M1-N201, P63, K65, S23, Zn0.5 for cabbage and M1-N157, P57, K116, S20, Zn0.5 Kg ha-1 for cauliflower) gave the maximum head and curd yields of cabbage and cauliflower, respectively. The levels of lime at the rate 2 t ha-1 (L3) provided the highest yields of cabbage and cauliflower in all locations. Dolomite lime @ 2 t ha-1 in combination with recommended fertilizer (M1L3) gave the highest yields and maximum economic returns of cabbage and cauliflower in all locations. However, it was identical with 1 t ha-1 of dolomite lime of similar dose of fertilizer nutrients. Therefore, application of lime at the rate 1 t ha-1 with STB recommended fertilizer management (M1) could be enough for profitable economic returns for cultivating cabbage and cauliflower in strongly acidic soil in Sylhet. Bangladesh Agron. J. 2016, 19(1): 49-57